1992
DOI: 10.3109/15563659209017948
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Systemic Poisoning After Skin Exposure to Monochloroacetic Acid

Abstract: Little information is available on the toxicity of monochloroacetic acid. We report the case of a 38 year-old man who was splashed with an 80% monochloroacetic acid solution on 25-30% of his body surface. In addition to epidermal and superficial dermal burns, features of systemic poisoning occurred within a few hours including disorientation, agitation, cardiac failure and coma. He later developed severe metabolic acidosis, rhabdomyolysis, renal insufficiency and cerebral edema, and died due to uncal herniatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 9 publications
3
38
0
1
Order By: Relevance
“…MCA has been widely used as an herbicide and an intermediate in the industrial synthesis of carboxymethylcellulose, phenoxyacetic acid, thioglycolic acid, glycine, and indigoid dyes (3). MCA is usually prepared as an 80% solution at 60°C for transport and industrial use (4).…”
Section: Introductionmentioning
confidence: 99%
“…MCA has been widely used as an herbicide and an intermediate in the industrial synthesis of carboxymethylcellulose, phenoxyacetic acid, thioglycolic acid, glycine, and indigoid dyes (3). MCA is usually prepared as an 80% solution at 60°C for transport and industrial use (4).…”
Section: Introductionmentioning
confidence: 99%
“…Rat studies using radiolabelled MCA showed a rapid accumulation in kidney, myocardium liver and small intestinal lumen (Kulling et al, 1992). In HUS platelet fibrin thrombi occur in capillaries, arterioles and sometimes arteries in the absence of vascular inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…There have been case reports of fatal systemic poisoning following skin exposure to MCA (Kulling et al, 1992;Kush et al, 1990). Toxic manifestations have included severe metabolic acidosis, rhadomyolysis, renal failure and cerebral edema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of poisoning include agitation, cardiac failure, metabolic acidosis, renal insufficiency and cerebral edema. 54 The suspected mechanism of action is interference with the Kreb's cycle and reaction with sulfhydryl groups in enzymes. 53,54 Dichloroacetate, which is thought to reactivate the Kreb's cycle and phenobarbitone which blocks membrane processes have been suggested as a treatments for monochloroacetic acid poisoning.…”
Section: Acids and Other Chemicals That Burn Skinmentioning
confidence: 99%